Towards Knowledge Organization Ecosystem (KOE). Issue 8 (25th October 2021) - Bagchi, Mayukh
Abstract: Increasingly, it has been hard to ignore that standalone KOSs are becoming functionally ineffective components for knowledge-based AI systems, given their inability to capture the continuous facetization and drift of domains. The paper proposes a radical re-conceptualization of KOSs as a first step to solve such an inability, and proposes: (i) a first theoretical characterization of Knowledge Organization Ecosystems (KOEs), (ii) as a consequence of such a novel characterization, a first examination and characterization of KOEs as Socio-Technical Systems (STSs), and (iii) motivating KOEs to be STSs which are grounded in AI ethics cardinals.